AJARAN TASAWUF DALAM PENGGABUNGAN TAREKAT QADARIYAH DAN NAQSYABANDIYAH PADA DZIKIR DALAM KITAB FATHUL AL-ARIFIN - Ihfanudin Saputra; Tatu Fajriah; Masykur (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2026)
This writing discusses the teachings of Sufism in the Qadiriyah Naqsyabandiyah tariqa within the manuscript titled Fathu Al-Arifin, authored by Syekh Ahmad Khatib Sambas on 9 Jumadil Awwal 1287 Hijriyah. In addition to addressing Sufi teachings, this writing also describes the physical condition of the manuscript, known in philological studies as codicology. This research is descriptive-qualitative in nature, employing a literature study method for data collection. The approach used in this research is the codicological approach. The results of this research reveal the presence of procedures (zikir guidelines) imbued with Sufi nuances in the Fathu Al-Arifin manuscript. These zikir guidelines are embodied in the practices of the Qadiriyah Naqsyabandiyah tariqa. Furthermore, the Fathu Al-Arifin manuscript also contains information on bai'at and talkin in the Qadiriyah Naqsyabandiyah tariqa. Syekh Ahmad Khatib Sambas combined two tariqas (Qadiriyah and Naqsyabandiyah) into one, namely the Qadiriyah Naqsyabandiyah tariqa, resulting in two zikir techniques in the Qadiriyah Naqsyabandiyah tariqa: nafi isbat (loud vocal zikir) and sirri ism dzat (silent heart-based zikir). The Qadiriyah tariqa practices jahri nafi isbat zikir (loud vocal), while the Naqsyabandiyah tariqa practices sirri ism dzat zikir (silent in the heart). There are four zikir methods in the Qadiriyah Naqsyabandiyah tariqa: perfection of suluk, adab, zikir, and muraqabah.